IMPLEMENTASI KEADILAN RESTORATIF DALAM PENYELESAIAN TINDAK PIDANA ANAK DI KEBUPATEN KARO STUDI KASUS KEJASAAN NEGERI KARO - Viktor Riusman Laia; Maslon Hutabalian; Hana Niken Julia Sihotang (Journal Recht (JR), 2025)
Restorative Justice (RJ) is an approach to resolving criminal cases that emphasizes victim recovery, perpetrator accountability, and community involvement. In the context of juvenile crime, this approach is an alternative solution to avoid the negative impacts of the conventional justice system on children in conflict with the law. This study aims to analyze the implementation of Restorative Justice in resolving juvenile crime cases at the Karo District Attorney's Office, by highlighting the principles of RJ and the factors that become obstacles in its implementation. The research method used is the normative juridical method with a qualitative approach. Data were obtained through interviews with prosecutors, supported by a study of related documents and regulation no. 15 of 2020 concerning RJ. The results of the study indicate that the implementation of Restorative Justice at the Karo District Attorney's Office refers to the main principles of RJ, namely restoration, participation, and balance of interests. However, there are several obstacles in its implementation, including the lack of public understanding of RJ, resistance from victims in accepting peace, and limited legal resources that support the optimal implementation of RJ. This study emphasizes the importance of increasing socialization of the concept of Restorative Justice to the community and strengthening regulations to support its more effective implementation in the juvenile criminal justice system.